Gates of the Arctic National Park and Preserve, Alaska : draft general management plan/environmental assessment, land protection plan, wilderness suitability review. - United States. National Park Service. Alaska Regional Office.; United States. National Park Service. (Anchorage, Alaska : U.S. Dept. of the Interior, National Park Service, Alaska Regional Office, 1985)
One folded col. map in pocket. "March 1985"--Cover. "NPS D-11." Bibliography: p. 263-269. Mode of access: Internet.